Gender Justice in Child Custody Disputes: The Maqāṣid al-Sharī‘ah Approach in Contemporary Judicial Practice - Farida Nurun Nazah; Restia Gustiana; Tobibatus Saadah; Ahmad Suryadi (MILRev: Metro Islamic Law Review, 2025)
Child custody disputes (ḥaḍānah) after divorce are a key issue in discussions of gender justice in Islamic family law, especially in Muslim-majority countries, including Indonesia. In this context, this study examines sixteen child custody decisions issued by religious courts in the Banten region, examining how the principles of maqāṣid al-sharī‘ah are applied in legal deliberations and the extent to which these decisions reflect the principles of gender justice and the best interests of the child. Using an integrated socio-legal approach and content analysis, this study examines the construction of legal reasoning from the decisions' content and the surrounding social context. Research findings indicate a shift in the legal reasoning of some judges towards a more substantive and contextual approach, taking into account the emotional, psychological, and social dimensions of children within the framework of hifẓ an-nafs and hifẓ annNasl. However, gender bias remains, including a tendency to place a higher burden of proof on mothers than fathers, and the influence of economic factors, which often outweigh the emotional well-being of the child. This study highlights the essence of incorporating the maqāṣid al-sharīʻah paradigm into judicial practice to ensure fair, responsive, and child-centered decisions. In addition to making a conceptual contribution to the reform of Islamic family law grounded in maqāṣid values, this study also recommends applying more appropriate jurisprudential guidelines to judges in adjudicating haḍānah cases, thereby consistently upholding the principles of substantive justice and gender equality.